2019
DOI: 10.1039/c9ay00600a
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics analysis in environmental samples – recent pyrolysis-gas chromatography-mass spectrometry method improvements to increase the reliability of mass-related data

Abstract: Thermal methods are of increased relevance in the field of mass-related microplastics (MP) analysis on trace level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 24 publications
0
126
1
Order By: Relevance
“…However, the lower the amount to be weighed, the higher the relative weighing error becomes and the more challenging it is to obtain a homogeneous mixture. So far, this has been one of the major drawbacks of Py-GC/MS (Fischer and Scholz-Böttcher, 2019). When combining Py-GC/MS with prior dissolution of polymers in an appropriate solvent such as TCB, stock solutions can be easily handled, quantitatively diluted or preconcentrated, and transferred directly into the pyrolyzer quartz tubes.…”
Section: Polymer Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lower the amount to be weighed, the higher the relative weighing error becomes and the more challenging it is to obtain a homogeneous mixture. So far, this has been one of the major drawbacks of Py-GC/MS (Fischer and Scholz-Böttcher, 2019). When combining Py-GC/MS with prior dissolution of polymers in an appropriate solvent such as TCB, stock solutions can be easily handled, quantitatively diluted or preconcentrated, and transferred directly into the pyrolyzer quartz tubes.…”
Section: Polymer Quantificationmentioning
confidence: 99%
“…Since those internal standards are not polymers, they probably behave differently than the polymer analytes when heated to typical pyrolysis temperatures of 600-800 • C. Particularly polycyclic aromatic hydrocarbons such as anthracene are thermally stable and more likely to evaporate instead of thermally decomposing along with the polymer analytes. Accordingly, Fischer and Scholz-Böttcher (2019) reported that the deuterated anthracene might have interacted with the inner surface of the pyrolyzer which eventually decreased repeatability. Though expensive, deuterated plastics (Dierkes et al, 2019) or specialized polymers like poly(3,4-ethylenedioxythiophene) typically used in semiconductor industry could be promising alternatives since they decompose in the same temperature range as the polymer analytes (Jin et al, 2013).…”
Section: Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that out of the 15 studies using Py-GC-MS for microplastic analysis, 11 used an in-house library or pyrograms from reference/standard polymers. 23,65,83,[118][119][120][121][122][123]126,128 The multitier confirmation approach using pyrogram and mass spectra provides higher confidence in the data quality. One distinct advantage of Py-GC-MS over the spectroscopic methods is that there is negligible effect of shape, density, surface topology, color, brightness, or opacity on the quality of the chemical match.…”
Section: Library Matching Proceduresmentioning
confidence: 99%
“…As mentioned by Tsuge et al (2011), there are different types of PUR. Only two studies, Fries et al (2013) and Fischer and Scholz-Böttcher (2019), respectively, studied unspecified PUR type at 700 C and methylene diphenyl diisocyanate polyurethane (MDI-PUR) at 590 C. The obtained compounds are different between the two studies; it is first due to the difference of temperature but also because of the use of TMAH in the study at 590 C. No marker has been proposed by the authors. More information concerning all the compounds obtained after the pyrolysis of PUR are given in Table 3.…”
Section: Identification Of Polymersmentioning
confidence: 99%